Impact of river discharge seasonality change on tidal duration asymmetry in the Yangtze River Estuary - Yu, Xiayan (Sci Rep, 2020)
The Yangtze River Estuary (YRE) is one of the world’s largest river-tidal systems with rapidly changing hydrology and morphology following the construction of multiple dams. The effects of dam construction may extend to the region close to the coast, where channel stability depends on the asymmetry of the tide. Here, we focus on the possible effects of changing discharge regimes on tidal asymmetry in the YRE. Specifically, we focus on the difference in duration between ebb and flood, quantified as tidal duration asymmetry, because it has strong implications for residual sediment transport and can be derived from available water level data. To cope with nonstationary tides under the influence of a time-varying river discharge, a nonstationary harmonic analysis tool (NS_TIDE) is applied to explore the spatiotemporal variations in tidal duration asymmetry, under the influence of different combinations of tidal constituents. Tidal duration asymmetry initially increases, then slightly decreases, in an upstream direction. It experiences significant seasonal variations in response to rapidly varying discharge: tides are more asymmetric upstream of Zhenjiang in the dry season and more asymmetric downstream in the wet season. The combined effects of discharge regulation and morphological changes cause seasonal alterations in tidal duration asymmetry. In the wet season, reduced river discharge caused by water storage and climate change enhance the asymmetry upstream (+11.74% at Wuhu, +7.19 at Nanjing) while the asymmetry is weakened downstream (−2.90% at Zhenjiang, −7.19 at Jiangyin) following the TGD’s operation. Downstream channel erosion caused by post-TGD lower sediment loads has become the dominant factor weakening tidal asymmetry in most parts of the YRE in the dry season. Understanding these evolutions of tidal duration asymmetry under the hydrological and morphological effects has important implications for the management of estuarine ecosystem and navigation.